Studies on the combined effects of titania and silicon carbide on the phase developments and properties of carbon-clay based ceramic composite. Issue 1 (1st January 2019) - Aramide, Fatai Olufemi; Adepoju, O. D.; Adediran, Adeolu Adesoji; Popoola, Abimbola Patricia
Abstract: Effects of titania (TiO2 ) and silicon carbide (SiC) on phase development and physico-mechanical properties of mullite-carbon were investigated. Powdered clay, kaolinite and graphite of predetermined compositions were blended with additives using ball mill for 3 h at 60 rev/min. Samples were produced by uniaxial compression and sintered between 1400°C and 1600°C for 1 h. They were characterized for various properties, phases developed and microstructural features. The addition of TiO2 and SiC in the sample lead to the formation of TiC in the sample at 1400°C and 1600°C. This takes place through high-temperature solid-state reaction (reaction sintering) of TiO2 and SiC. This also contributes to the reduction in the apparent porosity of the sample with increased sintering temperature. The presence of titania in the sample does not favour the stability of anorthite beyond 1400°C. The formation of 50.6% mullite in the sample at 1500°C made it have the highest cold crushing strength and absorbed energy. Young's modulus of the sample increased with increased sintering temperature. The sample sintered at 1500°C is considered optimum.